A lysosomal switch triggers proteostasis renewal in the immortal C. elegans germ lineage - Bohnert, K. Adam (Nature, 2017)
Although individuals age and die with time, an animal species can continue indefinitely, because of its immortal germ-cell lineage1. How the germline avoids transmitting damage from one generation to the next remains a fundamental question in biology. Here we identify a lysosomal switch that enhances germline proteostasis before fertilization. We find that Caenorhabditis elegans oocytes whose maturation is arrested by the absence of sperm2 exhibit hallmarks of proteostasis collapse, including protein aggregation. Remarkably, sperm-secreted hormones re-establish oocyte proteostasis once fertilization becomes imminent. Key to this restoration is activation of the vacuolar H(+)-ATPase (V-ATPase), a proton pump that acidifies lysosomes3. Sperm stimulate V-ATPase activity in oocytes by signalling the degradation of GLD-1, a translational repressor4 that blocks V-ATPase synthesis. Activated lysosomes, in turn, promote a metabolic shift that mobilizes protein aggregates for degradation, and reset proteostasis by enveloping and clearing the aggregates. Lysosome acidification also occurs during Xenopus oocyte maturation; thus, a lysosomal switch that enhances oocyte proteostasis in anticipation of fertilization may be conserved in other species.